Cephalothin: Review of Characteristics, Properties, and Status of Analytical Methods - Nascimento, Patricia Aleixa do [UNESP]; Kogawa, Ana Carolina; Nunes Salgado, Herida Regina [UNESP] (Oxford Univ Press Inc, 2021)
Background: Cephalothin (CET), a first generation cephalosporin, is the most efficient cephalosporin against resistant microorganisms. Many studies found in literature and pharmacopeias propose analytical methods which are most commonly HPLC and microbiological assays. Objective: This paper shows a brief review of analytical methods to quantify CET with a green analytical chemistry approach. Method: The research data were collected from the literature and official compendia. Results: Most of the analytical methods to determine CET were performed by HPLC and agar diffusion in pharmaceuticals, blood, urine, or water. Other analytical methods were found, such as UV-Vis, iodometry, fluorimetry, IR/Raman, electrochemical, and others in less quantity. One important aspect is that these methods use organic and toxic solvents like methanol and acetonitrile and only about 4% of the methods found use water as solvent. Conclusions: Research about analytical methods for CET focusing on green analytical chemistry is of great importance and could optimize its analysis in pharmaceutical industries and help to guarantee the quality of the product. More than just the development of new techniques, it is possible to enhance the ones that already exist, applying the green analytical chemistry principles. In this way, it will be possible to reduce the environmental impacts caused by other analytical procedures. Highlights: This work shows a brief review of literature and pharmacopeias of analytical methods to quantify CET. Its quality control can be updated to meet the needs of current analytical chemistry and to fit into sustainable and eco-friendly analysis.